The winnowing fan verse-essays in creative criticism - Norris, Christopher (Guides for the perplexed, 2017)
"This path-breaking book explores different ways in which writing about poetry can deepen and extend our critical engagement by deploying creatively the manifold resources of poetic language and form. Through a series of verse-essays, reflective monologues, and inventive variations on topics in literary theory The Winnowing Fan makes a strong case for revising received ideas about the scope and limits of criticism. Norris's poems traverse the full range of European poetic history from Homer's Odyssey, through the work of French symbolists such as Mallarm,̌ to modern writers such as Yeats, Benjamin, Heaney, Larkin, and Barthes. There are also verse-essays and shorter pieces on philosophers from Hume and Leibniz to Heidegger, Althusser, Derrida, de Man, Rorty, Deleuze, Badiou, and Agamben. In each case Norris seeks to free criticism from conventional academic forms and return it to an active mutual engagement with the practice of literature itself."--Bloomsbury Publishing